Urban Planning and E-Commerce: Understanding the Impact During Pandemic Covid-19 in Jakarta - Rahmatyas Aditantri; Febrina Mahliza; Alif Dimas Wibisono (Research Collaboration Community (RCC), 2021)
In this digital era, online shopping is kind of behaviour that many people do. E-commerce appears and can gradually replace the existence of conventional market. Especially, this behaviour increasing during this pandemic COVID-19. During the pandemic, there has been a change in habits and activities ranging from working from home, school from home to service trading activities starting to switch to an online service trading system. In order to manage sustainable urban planning, it is important to consider the likely effects of e-commerce. Increasing e-commerce can bring influence also impact to urban planning in a city. This research explores the consumer behaviour regarding e-commerce activities and the influence toward urban planning. DKI Jakarta is chosen as the study location and the policies related to the pandemic COVID-19 in Jakarta are also considered as a literature review. This research using expert judgement as a method of determining aspects of urban planning that are influenced by e-commerce activities and combining the analysis of planning documents and reports as well. Furthermore, e-commerce activities during pandemic COVID-19 in DKI Jakarta have several impacts in urban planning. The implication in urban planning still remains unclear since people still have hybrid consumer behaviour. Besides, it still takes a long time to see a significant impact toward e-commerce to urban planning in DKI Jakarta.